Effect of short-duration overnight cattle kraaling on grass production in a southern African savanna. Issue 4 (1st October 2016) - Sibanda, Pamela; Sebata, Allan; Mufandaedza, Edward; Mawanza, Mukai
Abstract : Ranch owners in eastern and southern Africa have embraced a new rangeland management practice of keeping cattle overnight in temporary livestock corrals (hereafter referred to as kraals) within rangelands for short durations (for example, one week) to improve grass production. To better understand the influence of this practice on the grass community, we determined grass species diversity, richness, biomass and quality (crude protein, fibre, rumen fermentation and metabolisable energy) from a chronosequence consisting of kraals abandoned 1, 2, 3 and 4 years prior to the study and compared them to the surrounding vegetation. Grass species diversity, richness, biomass and quality were higher in abandoned kraals than the surrounding vegetation. Grass biomass increased five-fold in the first year of kraal abandonment and thereafter declined three-fold after four years. Metabolisable energy, a measure of grass nutritive value, increased from 8.92 to 11.90 MJ kg−1 with kraaling. The number of grass species also increased with kraaling. Palatable grass species, such as Urochloa mosambicensis and Panicum maximum, were more abundant in abandoned kraal sites than the surrounding vegetation. We conclude that short-duration overnight cattle kraaling improves grass quality and biomass.